Visual impairments in tobacco use disorder. (January 2019) - Fernandes, Thiago P.; Silverstein, Steven M.; Almeida, Natalia L.; Santos, Natanael A.
Highlights: Overall findings reported small effects of smoking on visual processing. For the first time, a replication of these previous studies was performed. We found that visual processing impairments were pronounced in tobacco addiction disorder. These differences may explain the extended effects of tobacco constituents. Abstract: Prior studies found small effects of chronic smoking on spatial and color vision, but they were inconclusive. This study tries to: (1) replicate and extend these previous findings, and (2) rule in that this relationship is pronounced by tobacco addiction. Data were recorded in 71 healthy controls (M = 33.5 years; SD  = 5.4 years) and 63 individuals with tobacco addiction (M = 34.7 years; SD  = 4.8 years). Visual processing was assessed in the forms of contrast sensitivity for linear sine-wave gratings (spatial frequencies ranging between 0.2 and 16 cycles per degree) and color discrimination (using the Ellipse and Trivector subtests). The groups were matched for age, gender and level of education. The group with heavy smokers had reduced sensitivity for all spatial frequencies ( p  < .001), and impairments in color discrimination for both Trivector (all p -values < .001 for Protan, Deutan and Tritan) and Ellipse (all p -values < .001). This study consistently replicates and extended previous findings, and showed that visual processing can be strongly associated with tobacco addiction. These results indicate that excessive use of cigarettes, or chronic exposure to their compounds, affects visual discrimination, supporting the existence of overall deficits in visual processing in tobacco addiction.